Promoting Social Skills among Generation Alpha Learners with Special Needs - Heidi Flavian (MDPI AG, 2024)
Since digital learning and communication tools are ubiquitous, educators no longer need to teach Generation Alpha (GA) learners how to approach and use them. Nevertheless, while digital tools provide numerous advantages, researchers claim that the development of social skills is challenging for GA learners, given their lack of social experiences and interactions. These challenges are greater among learners with special needs (SNs). This study examines teachers' attitudes toward the integration of digital tools promoting social skills among GA learners with SNs, rather than focusing on academic skills. Twenty-one semi-structured interviews underwent qualitative analysis. Participants emphasized both the advantages and challenges of using digital tools and shared their perspectives regarding the possible effective use of these tools among learners with SNs.